2014
DOI: 10.2341/12-420-l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Surface Treatments on Bond Strength Between Resin Cements and Zirconia Ceramics

Abstract: This study compares the bond strength of resin cement and yttrium-stabilized tetragonal zirconia polycrystalline (Y-TZP) ceramic with different surface conditioning methods. Two hundred presintered Y-TZP ceramic specimens were prepared, sintered (4 × 4 × 4 mm), and randomly assigned to four equal groups as control (C, no conditioning); airborne particle abraded (APA, air abrasion with 11 μm Al2O3); tribochemical silica coating/silane coupling system (TSC, Rocatec, air abrasion with 110 μm Al2O3, 30 μm silica-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 35 publications
4
53
2
19
Order By: Relevance
“…Today there are many types of laser devices available in dental clinics. Related studies showed that the high intensity lasers like erbium:yttrium aluminum garnet (Er:YAG) lasers may more preferable to roughen the surface of high crystalline content ceramics [20,23,28,29]. The Er:YAG laser has the ability to remove particles by micro explosions and by vaporization, a process called ablation [20].…”
Section: Introductionmentioning
confidence: 98%
“…Today there are many types of laser devices available in dental clinics. Related studies showed that the high intensity lasers like erbium:yttrium aluminum garnet (Er:YAG) lasers may more preferable to roughen the surface of high crystalline content ceramics [20,23,28,29]. The Er:YAG laser has the ability to remove particles by micro explosions and by vaporization, a process called ablation [20].…”
Section: Introductionmentioning
confidence: 98%
“…Além disso, a cimentação adesiva oferece a vantagem de selar pequenas falhas na superfície interna criadas por corrosão ou jateamento de partículas, reforçando significativamente o material cerâmico. 6,7 Embora o uso da zircônia esteja, atualmente, bem estabelecido na Odontologia, não há um consenso sobre o protocolo ideal para a cimentação adesiva destas peças protéticas. 8 Durante os últimos quinze anos, os estudos têm se concentrado na busca por diferentes estratégias para se obter uma adequada cimentação adesiva Rev.…”
Section: Surface Treatment For the Adhesive Cementation Of Zirconia-bunclassified
“…16 No entanto, o jateamento induz a transformação da fase tetragonal para a fase monoclínica, desencadeando a propagação de microfissuras na cerâmica durante a função e isso diminui o desempenho a longo prazo da restauração em cerca de 20 a 30%. 2,6,[8][9][10]15,17,18 Shin et al 11 avaliaram o efeito de diferentes tratamentos de superfície sobre a força de união de dois diferentes cimentos resinosos contendo monômeros fosfatados à uma cerâmica à base de zircônia. Os autores concluíram que o jateamento com partículas de óxido de alumínio seguido da aplicação de um primer para zircônia alcançou o melhor resultado de união.…”
Section: Revisão Da Literatura/discussãounclassified
See 1 more Smart Citation
“…Options to airborne particle abrasion have been investigated, such as Er:YAG laser irradiation [61], silicabased film coatings [62], acid etching with dichloromethane (CH 2 Cl 2 ), and hot etching [63], Y-TZP particle deposition [64], and nonthermal plasma treatment [65]. Modifications to Y-TZP ceramic were also proposed.…”
Section: Clinical Considerations For Resin Bonding To Ceramicsmentioning
confidence: 99%